Effet de la fertilisation sur le rendement de l’espèce de la menthe verte - Chachoua, khadidja; Boughoufala, Keltouma (My University, 2018)
Mint is very popluar plant, grown in green and dry for tea.mint is the most popular plant in the world, it occuportant distribution in Algeria This work has been done in the Elbayadh region to study the effect of fertilizers on mint cultivation and to know the different menthods which improves the quality and the quantity of the yield which favord the increase of the economic profitability. Ourtest carried two different fertilizers (NPK, Urée 46) ,and the manure anda control soil not triturated the experimental model of our experiment on the cultivation of spearmint realize in the form of random blocks. The results showed that the effects ars highly significant on the parameters studied that the use of two fertilizers is more productive than the other treatments.
Keywords: The mint; fertilizer; manure; drip; yield; profitability; blocks,El Bayadh; Menthe; engrais; fumier; rendement; El Bayadh; rentabilité; blocs